Job satisfaction and turnover intention: A comprehensive review of the shared determinants - Jogi, S.; Vashisth, K. K.; Srivastava, S.; Alturas, B.; Kumar, D. (Human Systems Management, 2025)
Background Human capital is a critical asset for organizations, impacting financial performance and market value. Maintaining a stable, committed workforce is challenging. Job satisfaction emerges as a pivotal factor influencing employees’ intentions to leave or turnover intention. However, both encompass diverse dimensions that can exert positive or negative effects. Objectives To explore the common factors affecting job satisfaction and turnover intention, focusing on the significant positive and negative relationships. Method A systematic review based on the PRISMA framework has been conducted. The data has been precisely identified, evaluated, and extracted from the SCOPUS database based on set benchmarks. Result The investigation revealed a variety of determinants that exhibit a significant correlation with job satisfaction and turnover intention, manifesting in both positive and negative associations. Furthermore, these elements have been linked to established motivational theories, suggesting a theoretical underpinning for the observed relationships between workplace dynamics and employee behavior. Conclusion The result intended to provide a comprehensive understanding of the factors by offering a framework for studying job satisfaction and turnover intention guiding future research in the field of knowledge.